Ecological niche modeling and new distribution records of the central dwarf frog P. centralis Bokermann, 1962 (Anura, Leptodactylidae, Leiuperinae) with comments on its taxonomic status - Loebmann, Daniel; Giovanelli, João Gabriel Ribeiro [UNESP]; Mai, Ana Cecília Giacometti; Lyra, Mariana Lúcio [UNESP]; Brasileiro, Cinthia Aguirre; Haddad, Célio Fernando Baptista [UNESP] (Taylor & Francis, 2017)
Physalaemus centralis is distributed over open areas of eastern South America. Herein, we perform an extensive review of occurrence records and propose a potential distribution based on ecological niche modeling. In order to confirm species identification, as well taxonomic status along its distribution, we provide morphological and molecular data from analysed specimens. To reach our goals, we compiled data available in the literature and from scientific collections, as well as unpublished data. We identified records of P. centralis in 123 localities, 86 of those records remain unpublished. Consequently, it is possible to extend its range of distribution to the state of Rondônia, Brazil, and also to the Caatinga formation. The Maxent algorithm provided a model of potential distribution consistent with the distribution proposed here. Results indicate that P. centralis has a large distribution associated to open areas of South America (Cerrado, Caatinga and Pantanal), with no evidence that this is a case of species complex. The multiple approach proposed herein, that combines occurrence data from different sources and molecular data to confirm species identification, provided consistent results. Therefore, we recommend that this framework be used as a protocol to assess species distribution in future studies, especially in the case of widely distributed species.
Keywords: Cerrado domain; distribution; modeling; Physalaemus cuvieri group; species complex